Epitope profiling of monoclonal antibodies to the immunodominant antigen BmGPI12 of the human pathogen Babesia microti - Chand, Meenal; Choi, Jae-Yeon; Pal, Anasuya C.; Singh, Pallavi; Kumari, Vandana; Thekkiniath, Jose; Gagnon, Jacqueline; Timalsina, Sushma; Gaur, Gauri; Williams, Scott; Ledizet, Michel; Mamoun, Choukri Ben (Frontiers in Cellular and Infection Microbiology, 2022)
The significant rise in the number of tick-borne diseases represents a major threat to public health worldwide. One such emerging disease is human babesiosis, which is caused by several protozoan parasites of the Babesia genus of which B. microti is responsible for most clinical cases reported to date. Recent studies have shown that during its intraerythrocytic life cycle, B. microti exports several antigens into the mammalian host using a novel vesicular-mediated secretion mechanism. One of these secreted proteins is the immunodominant antigen BmGPI12, which has been demonstrated to be a reliable biomarker of active B. microti infection. The major immunogenic determinants of this antigen remain unknown. Here we provide a comprehensive molecular and serological characterization of a set of eighteen monoclonal antibodies developed against BmGPI12 and a detailed profile of their binding specificity and suitability in the detection of active B. microti infection. Serological profiling and competition assays using synthetic peptides identified five unique epitopes on the surface of BmGPI12 which are recognized by a set of eight monoclonal antibodies. ELISA-based antigen detection assays identified five antibody combinations that specifically detect the secreted form of BmGPI12 in plasma samples from B. microti-infected mice and humans but not from other Babesia species or P. falciparum.